Pengaruh Peer to Peer Lending, E-commerce, E-payment, dan Literasi Digital terhadap Kinerja UMKM Kota Medan dengan Literasi Keuangan sebagai Variabel Intervening - Butar, Riyani Butar; Pratomo, Wahyu Ario; Syafii, M. (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The study analyzes the influence of P2P lending, e-commerce, e-payment, and digital literacy on the performance of MSMEs in Medan City, mediated by financial literacy. Data were obtained through questionnaires and interviews with 95 assisted MSMEs, then processed using SEM-PLS with SmartPLS 4. This analysis found that directly, P2P lending, e-commerce, and digital literacy did not have a significant impact, while e-payment had a positive and significant impact on MSME performance. Indirectly, financial literacy only mediated the positive relationship between digital literacy and MSME performance, but did not mediate the relationship between P2P lending, e-commerce, and e-payment on MSME performance. This finding emphasizes the importance of strengthening digital and financial literacy as a strategy to improve MSME performance through digitalization.